1. X = Y let x=y
2. X*X = XY multiply by x on both sides
3. X*X - Y*Y = XY - Y*Y subtract y*y from both sides
4. (X+Y)(X-Y) = Y(X-Y) factorise
5. (X+Y) = Y divide by (x-y) on both sides
6. Y+Y = Y replace x with y
7. 2Y = Y factorise
8. 2 = 1 divide by y on both sides
Where lies the flaw in the logic?
Direct Link: www.brainbashers.com?ZIHG
Answer: On line 4 we are dividing both sides by (X-Y), now, since X=Y, this is 0. We are not allowed to divide by zero. This leads to a meaningless conclusion.
Unluckily, last week I lost my measuring tape. It was unlucky as I had to measure Daniel's toy box.
Luckily though I could remember that the top had an area of 720 square inches, the side was 800 square inches and the end was 360 square inches.
Take the alphabetic position of the first letter, half and then multiply by 1000.
F = 6, halved = 3, * 1000 = 3,000.